Association between body weight, physical activity and food choices among metropolitan transit workers - Hannan Peter J; Toomey Traci L; Harnack Lisa J; French Simone A (BMC, 2007)
Abstract Background Associations between body weight, physical activity and dietary intake among a population of metropolitan transit workers are described. Methods Data were collected during October through December, 2005, as part of the baseline measures for a worksite weight gain prevention intervention in four metro transit bus garages. All garage employees were invited to complete behavioral surveys that assessed food choices and physical activity, and weight and height were directly measured. Seventy-eight percent (N = 1092) of all employees participated. Results The prevalence of obesity (BMI >= 30 kg/m2) was 56%. Over half of the transit workers reported consuming fruit (55%) and vegetables (59%) ≥ 3/week. Reported fast food restaurant frequency was low (13% visited ≥ 3/week). Drivers reported high levels of physical activity (eg. walking 93 minutes/day). However, an objective measure of physical activity measured only 16 minutes moderate/vigorous per day. Compared to other drivers, obese drivers reported significantly less vigorous physical activity, more time sitting, and more time watching television. Healthy eating, physical activity and weight management were perceived to be difficult at the worksite, particularly among obese transit workers, and perceived social support for these behaviors was modest. However, most workers perceived weight management and increased physical activity to be personally important for their health. Conclusion Although transit workers' self-report of fruit and vegetable intake, and physical activity was high, perceived access to physical activity and healthful eating opportunities at the worksite was low. Obese workers were significantly less physically active and were more likely to report work environmental barriers to physical activity.